The Valachi papers - Maas, Peter 1929-2001 (New York Bantam Books, 1968)
Joe Valachi was one of the Mafia's most loyal soldiers. For more than thirty years he survived in an organization where failure means death. His career encompassed burglary, slot machines, shylocking, numbers, narcotics and, according to Justice Department estimates, 336 murders!
Includes index.
Keywords: Valachi, Joseph -- 1904-1971.; Mafia -- United States; Crime -- United States